Functional Profile of Human Cytomegalovirus Genes and Their Associated Diseases: A Review - Ye, Lele; Qian, Yunyun; Yu, Weijie; Guo, Gangqiang; Wang, Hong; Xue, Xiangyang (Frontiers in Microbiology, 2020)
The human cytomegalovirus (HCMV), whose genome is 235 ± 1.9 kbp long, is a common herpesvirus. However, the functions of many of its genes are still unknown. HCMV is closely associated with various human diseases and infects 60–90% of the global population. It can infect various human cells, including fibroblasts, epithelial cells, endothelial cells, smooth muscle cells, and monocytes. Although HCMV infection is generally asymptomatic and causes subtle clinical symptoms, it can generate a robust immune response and establish a latent infection in immunocompromised individuals, including those with AIDS, transplant recipients, and developing fetuses. Currently available antivirals approved for the treatment of HCMV-associated diseases are limited by dose-limiting toxicity and the emergence of resistance; however, vaccines and immunoglobulins are unavailable. In this review, we have summarized the recent literature on 43 newly identified HCMV genes. We have described their novel functions on the viral replication cycle, latency, and host immune evasion. Further, we have discussed HCMV-associated diseases and current therapeutic targets. Our review may provide a foundational basis for studies aiming to prevent and develop targeted therapies for HCMV-associated diseases.